Peran Perpustakaan dalam Pengembangan Literasi Siswa Di SD Inpres SP IV Manimeri - Triyuwono, Yuyun; Mauzizah, Alfri; Nisa, Kiki Alvia Khoirun; Suryanto, Suryanto (Librarium: Library and Information Science Journal, 2025)
This study aims to analyze the role of the library in developing student literacy at SD Inpres SP IV Manimeri. In the context of education, literacy is an important basic ability to support successful learning. The school library has a strategic role in providing resources that support the development of students' reading, writing and critical thinking skills. The method used in this research is a qualitative approach with data collection techniques using observation and interviews. The results showed that the school library at SD Inpres SP IV Manimeri made a significant contribution to increasing students' interest in reading and literacy skills although it was still less than optimal.  There are several challenges related to the maximum utilization of the library, such as the lack of relevant book collections and limited facilities and infrastructure.